The rationale for HPV-related oropharyngeal cancer de-escalation treatment strategies - Wierzbicka, Małgorzata; Szyfter, Krzysztof; Milecki, Piotr; Składowski, Krzysztof; Ramlau, Rodryg (Contemporary Oncology/Współczesna Onkologia, 2015)
The treatment paradigms for head and neck squamous cell cancer (HNSCC) are changing due to the emergence of human papillomavirus-associated tumors (HPV-related), possessing distinct molecular profiles and responses to therapy. Retrospective studies have suggested that HPV-related HNSCCs are more frequently cured than those caused by tobacco. Current clinical trials focus on the reduction of treatment-related toxicity and the development of HPV-targeted therapies. New treatment strategies include: 1) dose reduction of radiotherapy, 2) the use of cetuximab instead of cisplatin for chemo-radiation 3) less invasive surgical options, i.e. trans-oral robotic surgery and trans-oral laser microlaryngoscopy, and 4) more specific treatment attempts, including immunotherapeutic strategies, thanks to increasing comprehension of the molecular background of HPV-related HNSCC. Whereas recently published data shed light on immune mechanisms, other studies have focused on specific vaccination against HPV-related HNSCC. A crucial problem is patient selection to the chosen bias. Truly HPV-related cancers (p16-positive and HPV DNA-positive) with biomarkers for good response to therapy could be included in randomized trials aiming for less severe and better tailored therapy.